The Australian and New Zealand Society for Sarcopenia and Frailty Research (ANZSSFR) sarcopenia diagnosis and management task force: Findings from the consumer expert Delphi process. (8th December 2022) - Zanker, Jesse; Sim, Marc; Anderson, Kate; Balogun, Saliu; Brennan‐Olsen, Sharon L.; Dent, Elsa; Duque, Gustavo; Girgis, Christian M.; Grossmann, Mathis; Hayes, Alan; Henwood, Tim; Hirani, Vasant; et al.
Abstract: Objectives: To develop guidelines, informed by health‐care consumer values and preferences, for sarcopenia prevention, assessment and management for use by clinicians and researchers in Australia and New Zealand. Methods: A three‐phase Consumer Expert Delphi process was undertaken between July 2020 and August 2021. Consumer experts included adults with lived experience of sarcopenia or health‐care utilisation. Phase 1 involved a structured meeting of the Australian and New Zealand Society for Sarcopenia and Frailty Research (ANZSSFR) Sarcopenia Diagnosis and Management Task Force and consumer representatives from which the Phase 2 survey was developed. In Phase 2, consumers from Australia and New Zealand were surveyed online with opinions sought on sarcopenia outcome priorities, consultation preferences and interventions. Findings were confirmed and disseminated in Phase 3. Descriptive statistical analyses were performed. Results: Twenty‐four consumers (mean ± standard deviation age 67.5 ± 12.8 years, 18 women) participated in Phase 2. Ten (42%) identified as being interested in sarcopenia, 7 (29%) were health‐care consumers and 6 (25%) self‐reported having/believing they have sarcopenia. Consumers identified physical performance, living circumstances, morale, quality of life and social connectedness as the most important outcomes related to sarcopenia. Consumers either had no preference (46%) or preferred their doctor (40%) to diagnose sarcopenia and preferred to undergo assessments at least yearly (54%). For prevention and treatment, 46% of consumers preferred resistance exercise, 2–3 times per week (54%). Conclusions: Consumer preferences reported in this study can inform the implementation of sarcopenia guidelines into clinical practice at local, state and national levels across Australia and New Zealand.